Pengaruh strategi korporasi terhadap kinerja perusahaan foods & beverages di Indonesia selama pandemi covid-19 - Satya, Candra Harry; Nugroho, Antonius Agung; Patria, Harry (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to analyze 4 F&B companies listed on the Indonesia Stock Exchange (IDX), namely PT Indofood Sukses Makmur Tbk. (INDF.JK), PT. Mayora Indah Tbk. (MYOR.JK), PT Garudafood Putra Putri Jaya Tbk. (GOOD.JK), and PT Siantar Top Tbk. (STTP.JK). This study uses secondary data obtained from Yahoo Finance for the period March 11, 2020 to March 31, 2022. By using a Monte-Carlo simulation. Based on the results of the Monte-Carlo simulation, the sharpe ratio increased to 261.87% and volatility decreased to 43.16%. These results show that investment in the F&B sector in Indonesia is still very profitable and even experienced a fairly large increase in returns compared to before the COVID-19 pandemic. This is also in line with the government's prediction that with the economic recovery after the pandemic, the F&B industry sector in Indonesia will also grow. This study also found that during the COVID-19 pandemic, there was a significant change in the weight of the optimal investment portfolio, where GOOD.JK's performance far outperformed the other 3 companies due to the successful implementation of their corporate strategy in 2020 and 2021.